Analisis Pengaruh Rata-Rata Lama Sekolah, Pengeluaran Per Kapita, dan Pengangguran terhadap Indeks Pembangunan Manusia - Arin Ramadhiani Soleha; Moh. Faizin (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
This study aims to determine the effect of mean years of schooling, per capita expenditure, and unemployment on the human development index in districts/cities of East Java province in 2017-2021. The research method used is a quantitative method with a descriptive approach. Amount observations in this study is as many as 190 consisting of 38 districts/cities. The method of analysis of this study uses panel data regression analysis and significance test with the help of E-views 12. The results of this study explain that (1) Variable Mean Years of Schooling has a negative and significant effect on HDI. (2) The Per Capita Expenditure Variable has a negative and significant effect on HDI. (3) Unemployment variable has a negative and significant effect on HDI. (4) Variables Mean Years of Schooling, Expenditure Per Capita, and Unemployment simultaneously have a significant effect on HDI